DUA PULUH LIMA TAHUN FTMP DAN PEMBENTUKAN HABITUS DRAMATURGI TEATER PELAJAR DI NUSA TENGGARA BARAT - Taufik Mawardi; Nahdlatuzzainiyah; Yuga Anggana Sosani (Universitas Hamzanwadi, 2026)
The Festival Teater Modern Pelajar (FTMP) is one of the oldest and most sustainable student theatre festivals in West Nusa Tenggara, Indonesia. Having been organized twenty-five times and entering its twenty-sixth year in 2026, FTMP has long functioned as a platform for student theatre competition and artistic development. However, studies examining its long-term influence on the formation of dramaturgical practices among student theatre communities remain limited. This study aims to analyze the role of FTMP in shaping the dramaturgical habitus of student theatre groups in West Nusa Tenggara. This research employs a qualitative approach using Pierre Bourdieu’s sociological framework, particularly the concepts of field, habitus, and cultural reproduction. Data were collected through document analysis, festival archives, festival guidelines, media reports, and interviews with festival organizers and theatre practitioners. The data were analyzed using a descriptive-interpretative method to identify patterns of cultural reproduction within the festival ecosystem. The findings reveal that FTMP has evolved beyond a mere annual competition into a cultural field where organizers, judges, alumni, trainers, and student theatre groups interact and negotiate artistic values. Through festival regulations, judging mechanisms, alumni networks, and continuous training practices, FTMP contributes to the reproduction of specific artistic dispositions that shape the dramaturgical habitus of student theatre communities. This habitus is characterized by the dominance of social realism, linear dramatic structures, actor-centered performance practices, interpretative directing approaches, representational stage aesthetics, and the use of music as a dramatic reinforcement. This study demonstrates that FTMP has not only contributed to the growth of student theatre communities in West Nusa Tenggara but has also functioned as a cultural institution that shapes and reproduces dramaturgical traditions across generations. The findings provide a new perspective on the role of theatre festivals as agents of cultural reproduction and artistic formation within regional performing arts ecosystems.